2021
DOI: 10.1089/sur.2019.283
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Not an Independent Predictor of Necrotizing Soft Tissue Infection Outcomes

Abstract: Background: Necrotizing soft tissue infections (NSTIs) are a group of rapidly progressive infections of the skin and its underlying tissue. These infections result in substantial morbidity and mortality. The focus of this study was to determine if obesity is associated with a worsened clinical outcome or prolonged hospital course for patients with NSTIs. Patients and Methods: We conducted a retrospective chart review of patients with NSTI presenting to a single tertiary hospital. Fat content, measured with bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…There is limited data on the relationship between obesity and FG. In a retrospective study comparing normal weight patients with overweight patients (BMI> 25 kg/m2), weight was not found to have an effect on mortality (n=91, p=0.6) (19). In this study, mortality was not observed, and an effect of BMI on hospital stay was not found (p=0.1).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…There is limited data on the relationship between obesity and FG. In a retrospective study comparing normal weight patients with overweight patients (BMI> 25 kg/m2), weight was not found to have an effect on mortality (n=91, p=0.6) (19). In this study, mortality was not observed, and an effect of BMI on hospital stay was not found (p=0.1).…”
Section: Discussioncontrasting
confidence: 64%
“…While age, female gender, and DM are considered as risk factors for mortality, HT and COPD have not been shown to be associated with mortality. (10,15,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%